Avaliação do comportamento do cimento supersulfatado em concreto autoadensável - Homrich, Jefferson Teixeira Olea (2018)
SCC has the ability to flow through obstacles, filling the molds and resisting to segregation. However, this type of concrete has high cement paste-aggregate ratio, which causes higher heat release during cement hydration as well as higher susceptibility to retraction. Cements native from factory sub products are gaining attention due to environmental issues, being one of these the super sulfated cement (SSC). SSC has in its constitution granulated blast furnace slag (80%-90%), calcium sulfate (10-20%) and an alkaline activator (up to 5%), possibly Portland clinker. Besides low energy expense and a reduction in CO2 emission, SSC might stand out by its usage of factory waste which would be discarded to the environment. As its main characteristics, this type of binder presents low hydration heat release and higher formation of ettringite in the earlier ages, which could make it feasible to be used as a retraction compensator, characteristics desired in self-compacting concrete (SCC). This thesis studies the adequacy of SSC in SCC production, and for that reason SCC mixes were dosed using SSC and pozzolanic Portland cement type CP IV for benchmarks, as it is a low hydration heat release type of cement. Self-compacting tests were performed, as well as hydration heat tests, drying and plastic shrinkage, elasticity modulus at 28 days, axial compression resistance at the ages of 7, 28 and 56 days, water absorption at 28 days and SEM at 7 and 28 days of hydration. SCC’s produced with SSC presented superior results compared to CP IV cements that attended to the established limits is NBR 15823 (2010). SSC exhibited higher values for plastic shrinkage, but for drying shrinkage it presented retraction compensation at 28 days of hydration, showing inferior values compared to CP IV. SCC mixed with CP IV exhibited better performance on mechanical resistance, elasticity modulus and water absorption, but, despite its inferior resistance, SSC presented values that could be applied to a variety of situations in civil construction because its values reached around 40 MPa at 28 days.